2014
DOI: 10.1097/pgp.0b013e318290405a
|View full text |Cite
|
Sign up to set email alerts
|

Cox-2, EGFR, and ERBB-2 Expression in Cervical Intraepithelial Neoplasia and Cervical Cancer Using an Automated Imaging System

Abstract: We hypothesized that the activation of cyclooxygenase (COX)-2, epidermal growth factor receptor (EGFR), and ErbB-2 signaling is required for cervical intraepithelial neoplasia (CIN) lesions to progress to cervical cancer. A retrospective analysis was performed in 179 patients with Stage I squamous cell carcinoma (SCC) and 233 patients with CIN (112 CIN I, 47 CIN II, and 74 CIN III). COX-2, EGFR, and ErbB-2 expression was analyzed by immunohistochemistry using the ACIS III automated imaging system. The mean exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…In physiological processes, EGFR regulates cell differentiation and the cell cycle, and also promotes repair of wound tissue. In pathological processes, overexpression of EGFR has been observed in a variety of human cancers, such as breast, gastric, and cervical cancers [17-19]. The overexpression of EGFR continuously transmits signals to cells, which interfere with the normal regulation of cell differentiation and cycle, which in turn contribute to cells’ continued proliferation and malignant transformation [20].…”
Section: Discussionmentioning
confidence: 99%
“…In physiological processes, EGFR regulates cell differentiation and the cell cycle, and also promotes repair of wound tissue. In pathological processes, overexpression of EGFR has been observed in a variety of human cancers, such as breast, gastric, and cervical cancers [17-19]. The overexpression of EGFR continuously transmits signals to cells, which interfere with the normal regulation of cell differentiation and cycle, which in turn contribute to cells’ continued proliferation and malignant transformation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of S1PR2-COX-2 is a key enzyme involved in production of prostaglandins and has been implicated in various cell transformations including cholangiocytes (21)(22)(23)(24)(25). Previous studies reported that CBAs induced COX-2 expression and promoted growth in human CCA cells in culture (15,16).…”
Section: Tca Induces Cox-2 Expression and Chronic Inflammation Viamentioning
confidence: 99%
“…Cox2, which is involved in inflammatory processes, has been found to play a key role in prostaglandin biosynthesis (8,9). Generally, the cox2 protein is only expressed in a limited number of cell types, whereas overexpressed in a variety of malignant tumors, suggesting its possible role in carcinogenesis (6,(10)(11)(12)(13)(14)(15). Moreover, several mediatory factors, such as tumor promoters, proinflammatory cytokines and growth factors, have been reported to induce the upregulation of cox2 expression (16).…”
Section: Introductionmentioning
confidence: 99%